The Influence of Organizational Culture and Principal’s Academic Supervision on Teacher’s Performance at SMA Negeri 1 Gunung Megang - Lestari, Sri; Ahmad, Syarwani; Rohana, Rohana (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
Teachers are one of the main components that determine the success of a school in achieving its goals because teachers are the transferors of knowledge in learning. Performance or work achievement can be interpreted as the achievement of a person’s work, but in reality, there are still many teachers whose performance is less than optimal. So that teachers can improve their performance, the role of the principal as supervisor is needed. This research will be carried out at SMA Negeri 1 Gunung Megang. This research uses descriptive research type. The results obtained show that there is an influence on each variable, namely, that there is a significant influence of organizational culture on teacher performance 98.6%, there is a significant influence of the principal’s academic supervision on teacher performance 83.3% and there is a significant influence of organizational culture and academic supervision of the principal together on teacher performance 99.2%. Meanwhile, the remaining 0.8% is influenced by other factors that are not included in this research.